The Association between the Montreal Cognitive Assessment and Functional Activity Questionnaire in the Systolic Blood Pressure Intervention Trial (SPRINT) - Still, Carolyn H (Arch Clin Neuropsychol, 2018)
OBJECTIVE: To examine the association of global cognitive function assessed via the Montreal Cognitive Assessment (MoCA) and deficiencies in instrumental activities of daily living (IADL) on the Functional Activity Questionnaire (FAQ) in hypertensive older adults in the Systolic Blood Pressure Intervention Trial (SPRINT). METHODS: In cross-sectional analysis, 9,296 SPRINT participants completed the MoCA at baseline. The FAQ was obtained from 2,705 informants for SPRINT participants scoring <21 or <22 on the MoCA, depending on education. FAQ severity ranged from no dysfunction (Score = 0) to moderate/severe dysfunction (Score = 5+). RESULTS: Participants who triggered FAQ administration were older, less educated, and more likely to be Black or Hispanic (p < 0.001). Sixty-one percent (n = 1,661) of participants’ informants reported no functional difficulties in IADLs. An informant report, however, of any difficulty on the FAQ was associated with lower MoCA scores after controlling for age, sex, race/ethnicity, and education (p < 0.05). Partial proportional odds regression indicates that participants scoring lower on the MoCA (in the 10th to <25th, fifth to <10th, and <fifth percentiles) had higher adjusted odds of their informant indicating dysfunction on the FAQ, relative to participants scoring at or above the 25th percentile on the MoCA (p < 0.001). CONCLUSIONS: While lower global cognitive function was strongly associated with IADL deficits on FAQ, informants indicated no functional difficulties for the majority of SPRINT participants, despite low MoCA scores. These findings can help with designing future studies which aim to detect mild cognitive impairment and/or dementia in large, community-dwelling populations.